Infants' visual exploration strategies for adult and child faces. (24th January 2022) - Conte, Stefania; Baccolo, Elisa; Bulf, Hermann; Proietti, Valentina; Macchi Cassia, Viola
Abstract: By the end of the first year of life, infants' discrimination abilities tune to frequently experienced face groups. Little is known about the exploration strategies adopted to efficiently discriminate frequent, familiar face types. The present eye‐tracking study examined the distribution of visual fixations produced by 10‐month‐old and 4‐month‐old singletons while learning adult (i.e., familiar) and child (i.e., unfamiliar) White faces. Infants were tested in an infant‐controlled visual habituation task, in which post‐habituation preference measured successful discrimination. Results confirmed earlier evidence that, without sibling experience, 10‐month‐olds discriminate only among adult faces. Analyses of gaze movements during habituation showed that infants' fixations were centered in the upper part of the stimuli. The mouth was sampled longer in adult faces than in child faces, while the child eyes were sampled longer and more frequently than the adult eyes. At 10 months, but not at 4 months, global measures of scanning behavior on the whole face also varied according to face age, as the spatiotemporal distribution of scan paths showed larger within‐ and between‐participants similarity for adult faces than for child faces. Results are discussed with reference to the perceptual narrowing literature, and the influence of age‐appropriate developmental tasks on infants' face processing abilities.